An Analysis on Nurse Knowledge and Attitude on Pre-Hospital Ambulance Service Satisfaction in Bali, Indonesia - I Wayan Edi Sanjana; Titin Andri Wihastuti; Nurul Muslihah (Babali Nursing Research, 2022)
Introduction: The ambulance service quality has a great impact on well-being and survival of emergency patients. The patient satisfaction was one of main metrics to assess ambulance service and an indicator of quality to manage pre-hospital emergency service. This research was aimed to analyze the correlation between nurse knowledge and attitude and satisfaction of pre-hospital ambulance service in Bali, Indonesia. Methods: This research exerted correlative analytic method and cross-sectional approach. Moreover, this research involved as many as 271 respondents who were consisted of 127 nurses and 144 patients. The cluster sampling technique was used to select the research respondents. Results: The analysis result of Spearman’s rank test referred the knowledge (p = 0,001; r = 0,269) and attitude (p = 0,000; r = 0,307) significantly have a positive relation to the pre-hospital ambulance service satisfaction in Bali. Conclusion: The result of multiple linear regression test referred that the nurse attitude was a dominant factor which related to the pre-hospital ambulance service satisfaction in Bali. Therefore, it needed to conduct a periodical formal training in order to increase the quality of ambulance nurse service which could affect the increase of pre-hospital ambulance service satisfaction in Bali, Indonesia.